Complex ATP7B mutation patterns in Wilson disease and evaluation of a yeast model for functional analysis of variants. Issue 5 (14th February 2019) - Li, Xiaojin; Zhang, Wei; Zhou, Donghu; Lv, Tingxia; Xu, Anjian; Wang, Hejing; Zhao, Xinyan; Zhang, Bei; Li, Yanmeng; Jia, Siyu; Wang, Yu; Wang, Xiaoming; et al.
Abstract: Wilson disease (WD) is a rare autosomal recessive genetic disorder that is associated with various mutations in the ATP7B gene. Although ATP7B variants are frequently identified, the exact mutation patterns remain unknown because of the absence of pedigree studies, and the functional consequences of individual ATP7B variants remain to be clarified. In this study, we recruited 65 clinically diagnosed WD patients from 60 unrelated families. Pedigree analysis showed that besides several ATP7B homozygous variants (8/65, 12.3%), compound heterozygous variants (43/65, 66.2%) were present in the majority of WD patients. There were 20% of the patients had one (12/65, 18.5%) or multiple (1/65, 1.5%) variants in only a single allele, characterized by a high ratio of splicing or frameshift variants. Nine ATP7B variants were cloned into the pAG426GPD yeast expression vector to evaluate their functional consequences, and the results suggested different degrees of functional disruption from mild or uncertain to severe, consistent with the corresponding phenotypes. Our study revealed the complex ATP7B mutation patterns in WD patients and the applicability of a yeast model system to the evaluation of the functional consequences of ATP7B variants, which is essential for WD cases that are difficult to interpret.